Impact and consequences of lowly pathogenic bird influenza H9N2 on indus-trial layers - S. M. Senyushkin; A. V. Kolechko (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Avian Influenza – is a disease that affects birds and mammals, including humans. It is caused by a virus that is highly capable of genetic and antigenic variations and has characteristic biological properties, including pathogenicity and replication among different species. In addition to its ability to infect animals and cause more or less severe diseases in them, the influenza virus can also spread among people and cause death. Avian influenza is a disease caused by the influenza virus in bird populations, particularly in poultry and commercial poultry, which leads to significant economic losses. Avian influenza virus is present in wild bird populations, especially waterfowl, where it is maintained and evolves and can be transmitted from them to domestic animals, including pigs and poultry. Therefore, poultry farms near water bodies and ponds are at increased risk as they may attract wild waterfowl and other migratory birds. Nevertheless, it is very important to emphasize that not all avian influenza viruses have the same ability to infect people. Here it is relevant to note the low-pathogenic avian influenza virus H9N2, which began spreading in Ukraine in 2021 and caused huge economic losses. The losses were caused by the emergence of an incomprehensible respiratory complex, reduced productivity in commercial and family flocks, deterioration in egg quality, and increased mortality of poultry with complicated etiology. Low pathogenicity avian influenza (LPAI) – means an infection of poultry or other birds caused by the influenza A virus. This complex disease is caused by viruses divided into several subtypes, H5 and H7, H9, but which do not fall under the definition of HPAI. They belong to the Orthomyxoviridae family and are segmented RNA viruses. Influenza A viruses based on hemagglutinin H are divided into 16 subtypes. In addition to the H antigen, influenza viruses have one of nine neuraminidase antigens (N). Each type of avian influenza virus has one hemagglutinin and one neuraminidase antigen, in any combination. The disease occurs worldwide, but different subtypes are more common in certain regions than others. Rheosartans have also begun to appear when a single cell is infected with different viruses. Since this infection is new in Ukraine and very dangerous for industrial poultry farming, I consider it expedient to study and highlight the growing problem.